Thermal stability and flame-retardant properties of a basalt/kevlar fiber-reinforced hybrid polymer composite with bran filler particulates - N. Beemkumar; Ganesan Subbiah; Vijay J. Upadhye; Arpit Arora; Shakti Prakash Jena; K Kamakshi Priya; Habtamu Alemayehu (Results in Engineering)
The development of advanced polymer composites with enhanced thermal stability and flame-retardant properties is essential for high-performance applications. This study aims to investigate a novel hybrid polymer composite reinforced with basalt and Kevlar fibers, integrated with bran filler particulates within an epoxy matrix. The composite was fabricated using the conventional hand layup technique, and its thermal and flame-retardant properties were systematically analyzed. Thermogravimetric analysis (TGA) revealed excellent thermal stability, with significant weight loss occurring only above 350 °C. The coefficient of linear thermal expansion (CLTE) was measured at 1.74 × 10⁻⁵ / °C, indicating superior dimensional stability under thermal stress. Thermal conductivity tests demonstrated an improved value of 0.79 W/mK, attributed to the efficient heat dissipation properties of basalt fibers. Heat deflection temperature (HDT) testing indicated a high HDT of 179 °C, showcasing resistance to deformation under heat. Furthermore, the composite exhibited enhanced flame-retardant capacity due to the synergistic effects of basalt and Kevlar fibers and the char-forming properties of bran fillers. The findings highlight the novelty of combining basalt and Kevlar fibers with bran particulates to achieve superior thermal and flame-retardant properties. This hybrid composite demonstrates significant potential for applications in thermal insulation and protective materials where high thermal stability and fire resistance are essential.